Use of E-Learning Tools in Teaching and Learning English - Vinay Kumar, K.; Babu Palukuri, Vijaya; Noorie Banu, Syeda (International Journal of Psychosocial Rehabilitation, 2024)
Information and communication technology (ICT) plays a pivotal role in every walk of life in the present world. The teaching methodology has undergone a profound transformation due to the prevalence of technology and its tools. Technology and e-learning have become buzzwords during the COVID-19 pandemic. The world has shut down for the first time, and all the educational institutions are closed with uncertainty of their reopening. There is no chance of conducting classroom-based teaching and learning. At this juncture, the compelled option is online teaching and learning. This paper introduces some of the useful tools and techniques to overcome the problem of classroom teaching learning English. It also helps to learn language skills independently. These tools provide opportunities for motivating students learning and collaborative nuance. The majority of the tools which are discussed in the paper can be used for the enhancement of four skills (LSRW) of language